Investigating the Role of Self-selected STEM Projects in Fostering Student Autonomy and Self-directed Learning - Tang, Kok-Sing; McLure, Felicity; Williams, John; Donnelly, Catherine (Springer Nature, 2024)
Research in STEM education has focussed on integrated STEM projects that combine knowledge and skills across science, technology, engineering, and mathematics. These integrated STEM projects are typically designed by teachers or researchers addressing a limited range of topics that do not always cater well to the diversity of interest among children and adolescents. By contrast, self-selected projects where students have more choices and autonomy in selecting their own projects are relatively rare. Consequently, there is a gap in the literature on students’ learning experiences when they choose and develop their own STEM projects. This study aims to examine the classroom experience and enactment of a high school STEM course designed for Grade 9 and 10 students (14 to 16 years old) to carry out a project of their choice aligned with the theme of sustainability. A case study methodology was used to investigate eight students’ lived experiences in making connections to STEM. The study reveals the nature of students’ self-directed learning experiences as they chose their own topics of exploration and subsequently developed their respective STEM-related projects. It also illuminates the alignments and tensions between STEM integration and various aspects of students’ self-directed learning, including intrinsic motivation, open-ended tasks, goal setting, design thinking, collaboration with external partners, curriculum constraint, and time management. The implications of the study encompass student autonomy and agency, the significance of authentic problems and themes in STEM education, and the role of curriculum in facilitating self-selected projects.